Real-world Outcome of Patients with Advanced Renal Cell Carcinoma and Intermediate- or Poor-risk International Metastatic Renal Cell Carcinoma Database Consortium Criteria Treated by Immune-oncology Combinations: Differential Effectiveness by Risk Group - Santoni, Matteo; Buti, Sebastiano; Myint, Zin W; Maruzzo, Marco; Iacovelli, Roberto; Pichler, Martin; Kopecky, Jindrich; Kucharz, Jakub; Rizzo, Mimma; Galli, Luca; Büttner, Thomas; De Giorgi, Ugo; et al. (European urology oncology, 2024)
BACKGROUND: Renal c carcinoma (RCC) is one of the most common urinary cancers worldwide, with a predicted increase in incidence in the coming years. Immunotherapy, as a single agent, in doublets, or in combination with anti-vascular endothelial growth factor receptor tyrosine kinase inhibitors (TKIs), has rapidly become a cornerstone of the RCC therapeutic scenario, but no head-to-head comparisons have been made. In this setting, real-world evidence emerges as a cornerstone to guide clinical decisions. OBJECTIVE: The objective of this retrospective study was to assess the outcome of patients treated with first-line immune combinations or immune oncology (IO)-TKIs for advanced RCC. DESIGN, SETTING, AND PARTICIPANTS: Data from 930 patients, 654 intermediate risk and 276 poor risk, were collected retrospectively from 58 centers in 20 countries. Special data such as sarcomatoid differentiation, body mass index, prior nephrectomy, and metastatic localization, in addition to biochemical data such as hemoglobin, platelets, calcium, lactate dehydrogenase, neutrophils, and radiological response by investigator's criteria, were collected. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Overall survival (OS) and progression-free survival (PFS) were estimated using the Kaplan-Meier method. The median follow-up was calculated by the inverse Kaplan-Meier method. RESULTS AND LIMITATIONS: The median follow-up time was 18.7 mo. In the 654 intermediate-risk patients, the median OS and PFS were significantly longer in patients with the intermediate than in those with the poor International Metastatic Renal Cell Carcinoma Database Consortium (IMDC) criteria (38.9 vs 17.3 mo, 95% confidence interval [CI] p < 0.001, and 17.3 vs 11.6 mo, 95% CI p < 0.001, respectively). In the intermediate-risk subgroup, the OS was 55.7 mo (95% CI 31.4-55.7) and 40.2 mo (95% CI 29.6-51.6) in patients treated with IO + TKI and IO + IO combinations, respectively (p = 0.047). PFS was 30.7 mo (95% CI 16.5-55.7) and 13.2 mo (95% CI 29.6-51.6) in intermediate-risk patients treated with IO + TKI and IO + IO combinations, respectively (p < 0.001). In the poor-risk subgroup, the median OS and PFS did not show a statistically significant difference between IO + IO and IO + TKI. Our study presents several limitations, mainly due to its retrospective nature. CONCLUSIONS: Our results showed differences between the IO + TKI and IO + IO combinations in intermediate-risk patients. A clear association with longer PFS and OS in favor of patients who received the IO + TKI combinations compared with the IO-IO combination was observed. Instead, in the poor-risk group, we observed no significant difference in PFS or OS between patients who received different combinations. PATIENT SUMMARY: Renal cancer is one of the most frequent genitourinary tumors. Treatment is currently based on immunotherapy combinations or immunotherapy with tyrosine kinase inhibitors, but there are no comparisons between these.In this study, we have analyzed the clinical course of 930 patients from 58 centers in 20 countries around the world. We aimed to analyze the differences between the two main treatment strategies, combination of two immunotherapies versus immunotherapy + antiangiogenic therapy, and found in real-life data that intermediate-risk patients (approximately 60% of patients with metastatic renal cancer) seem to benefit more from the combination of immunotherapy + antiangiogenic therapy than from double immunotherapy. No such differences were found in poor-risk patients. This may have important implications in daily practice decision-making for these patients.
Keywords: nádory ledvin; karcinom z renálních buněk; Tyrosine Kinase Inhibitors; Carcinoma, Renal Cell; retrospektivní studie; Humans; výsledek terapie; lidé; inhibitory tyrosinkinasy; Retrospective Studies; Kidney Neoplasms; Treatment Outcome